2000
DOI: 10.1523/jneurosci.20-22-08474.2000
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Topography of Corticopontine Projections from Rat Barrel Cortex: Correlations with Corticostriatal Organization

Abstract: Subcortical re-entrant projection systems connecting cerebral cortical areas with the basal ganglia and cerebellum are topographically specific and therefore considered to be parallel circuits or "closed loops." The precision of projections within these circuits, however, has not been characterized sufficiently to indicate whether cortical signals are integrated within or among presumed compartments. To address this issue, we studied the first link of the rat cortico-ponto-cerebellar pathway with anterograde a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
106
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(120 citation statements)
references
References 72 publications
13
106
1
Order By: Relevance
“…The ipsilateral contribution of cerebrocerebellar connections correlated nicely with the laterality of the CTb labeling in the pontine nuclei suggesting that this ipsilateral connection predominantly stems from the bilateral projection of the pontine nuclei to the cerebellar cortex (Serapide et al, 2002) rather than from a bilateral corticopontine projection (Legg et al, 1989;Leergaard et al, 2000b). Although the ipsilateral distribution of cortical RV labeling was similar to that observed contralaterally, local differences in density were observed; e.g., the density of the rostral M1/M2 patch was usually increased with respect to the ipsilateral main patch of labeling (Fig.…”
Section: Bilateral Labelingmentioning
confidence: 73%
See 1 more Smart Citation
“…The ipsilateral contribution of cerebrocerebellar connections correlated nicely with the laterality of the CTb labeling in the pontine nuclei suggesting that this ipsilateral connection predominantly stems from the bilateral projection of the pontine nuclei to the cerebellar cortex (Serapide et al, 2002) rather than from a bilateral corticopontine projection (Legg et al, 1989;Leergaard et al, 2000b). Although the ipsilateral distribution of cortical RV labeling was similar to that observed contralaterally, local differences in density were observed; e.g., the density of the rostral M1/M2 patch was usually increased with respect to the ipsilateral main patch of labeling (Fig.…”
Section: Bilateral Labelingmentioning
confidence: 73%
“…To some extent this is due to the complex transformations that take place in the cerebro-ponto-cerebellar pathway (Leergaard et al, 2006). Approaches to understand its functional organization are hampered by its multisynaptic nature and complex organization (Leergaard et al, 2000b(Leergaard et al, , 2006; e.g., only scant information is available on the relation between the functional cerebral regions and the so-called fractured cerebellar maps (Welker, 1987;Bower, 2011) or with the olivocerebellar modules. These modules are based on the matching organizations of projections from the olivocerebellar climbing fibers to longitudinal strips or zones of the Purkinje cells, the projections from these Purkinje cells to the cerebellar nuclei and their subsequent and selective projection patterns Teune et al, 2000;Sugihara and Shinoda, 2004;Voogd and Ruigrok, 2004;Pijpers et al, 2005;Apps and Hawkes, 2009;Ruigrok, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Posteriorparietal injections were designed as a control intervention and demonstrate that the effects of PSI on motor learning are specific to motor cortex. The cerebellum has a lateralized organization, although the degree of lateralization may be less than in motor cortex (Luft et al, 1998;Leergaard et al, 2000;Matsushita and Xiong, 2001). However, even with unilateral PSI, some dampening of the learning curve would be expected if protein synthesis in cerebellar cortex is required for skill learning.…”
Section: Discussionmentioning
confidence: 99%
“…To mediate somesthesia-guided behaviors, specific parts of the neural substrate must convey somatosensory information to the motor system. In rodents, for example, tracing studies have shown that primary somatosensory (SI) cortex projects to many brain regions involved in motor control including the primary motor (MI) cortex, neostriatum, superior colliculus, and the pontine nuclei (Wise and Jones, 1977a;Wiesendanger and Wiesendanger, 1982;Donoghue and Parham, 1983;Mihailoff et al, 1985;McGeorge and Faull, 1989;Miyashita et al, 1994;Izraeli and Porter, 1995;Schwarz and Thier, 1995;Brown et al, 1998;Wright et al, 1999;Leergaard et al, 2000aLeergaard et al, , 2003. Because MI cortex and superior colliculus project directly to motor nuclei in the brainstem and spinal cord (Liang et al, 1991;Imai and Aoki, 1993;Miyashita and Mori, 1995), SI projections to these regions provide a relatively direct route by which somatosensory information may modulate behavior.…”
mentioning
confidence: 99%